2022
DOI: 10.1088/1748-605x/ac6b07
|View full text |Cite
|
Sign up to set email alerts
|

The additive effects of photobiomodulation and bioactive glasses on enhancing early angiogenesis

Abstract: Early angiogenesis is important to facilitate biomaterials’ osteogenic effects and avoid the bone regeneration failure for large-sized bone defects. Bioactive glasses (BG) have been widely utilized as a biomaterial for bone repair. However, the early angiogenesis of BG may be inadequate. In this study, we explored the effects of photobiomodulation (PBM) combined with BG on early angiogenesis to solve this bottleneck problem of insufficient early angiogenesis. In vitro, human umbilical vein endothelial cells (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…On the other hand, the osteoinductivity of BG also overcomes the application limitations of the PBM. Our previous study [ 22 ] found that the combination of BG and PBM could additively promote early angiogenesis. Therefore, we preliminarily explored their additive effects on promoting bone regeneration in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the osteoinductivity of BG also overcomes the application limitations of the PBM. Our previous study [ 22 ] found that the combination of BG and PBM could additively promote early angiogenesis. Therefore, we preliminarily explored their additive effects on promoting bone regeneration in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the enhanced early angiogenesis may promote bone regeneration and accelerate bone defect healing. In our recently published paper, we used BG and PBM in combination to observe their effects on angiogenesis [ 22 ]. We found that the superiority of PBM on angiogenesis could overcome the inadequacy of BG in early angiogenesis, and the combination of both would generate additive effects on enhancing human umbilical vein endothelial cells’ proliferation, angiogenic-related growth factors’ gene expression and tubules formation in vitro , as well as promoting early angiogenesis in vivo [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations